Front Cover: (Adv. Sci. 19/2022). Issue 19 (6th July 2022) - Unknown
Abstract : Functional Carbon‐Rich Materials — Anniversary Issue for Klaus Müllen This special issue aims to celebrate the 75th birthday of Professor Klaus Müllen and highlights his achievements and impact on a wide range of areas involving functional carbon‐rich materials. We would like to honor a remarkable chemist, a visionary researcher and an inspiring teacher for several generations of chemists and materials scientists worldwide, who has stimulated and shaped this research field over several decades. Further information can be found in article 2203029 . Cover design: Yanwei Gu.